2017
DOI: 10.1038/s41598-017-03837-z
|View full text |Cite
|
Sign up to set email alerts
|

Integration of DNA methylation and gene transcription across nineteen cell types reveals cell type-specific and genomic region-dependent regulatory patterns

Abstract: Despite numerous studies done on understanding the role of DNA methylation, limited work has focused on systems integration of cell type-specific interplay between DNA methylation and gene transcription. Through a genome-wide analysis of DNA methylation across 19 cell types with T-47D as reference, we identified 106,252 cell type-specific differentially-methylated CpGs categorized into 7,537 differentially (46.6% hyper- and 53.4% hypo-) methylated regions. We found 44% promoter regions and 75% CpG islands were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…All report a high overall correlation between DNA methylation of the same samples measured using different methods. Not all of these studies commented on individual CpG site correlation; however, manual inspection of the correlation scatter plots reveals that a subset of CpGs shows large differences in methylation values between the platforms being compared [1,[15][16][17][18]. Altogether, these studies demonstrate that some CpGs reproduce poorly, regardless of sample type or method used.…”
Section: Discussionmentioning
confidence: 99%
“…All report a high overall correlation between DNA methylation of the same samples measured using different methods. Not all of these studies commented on individual CpG site correlation; however, manual inspection of the correlation scatter plots reveals that a subset of CpGs shows large differences in methylation values between the platforms being compared [1,[15][16][17][18]. Altogether, these studies demonstrate that some CpGs reproduce poorly, regardless of sample type or method used.…”
Section: Discussionmentioning
confidence: 99%
“…49 Epigenetic DNA modifications occur in prokaryotic and eukaryotic cells. 50,51 However, little is known about the role of such nucleic acid changes in controlling spurious transcription initiation. To date, the best characterised consequences are those identified in mouse embryonic stem cells, 52 where intragenic methylation of CpG dinucleotides within the body of genes is required to prevent intragenic transcription initiation by RNA polymerase II.…”
Section: Inhibition Of Spurious Transcription Initiationmentioning
confidence: 99%
“…Past studies examining the similarity of measurements in 450K and pyrosequencing in cell lines and brain tissue [9,14] have also observed that some CpG sites do not reproduce. Moreover, comparisons of 450K to whole genome bisulfite sequencing showed the same conclusions [1,15,16] as did reduced representation bisulfite sequencing [17,18]. Multiple published manuscripts have described the correlation of CpG sites measured using different methods.…”
Section: Discussionmentioning
confidence: 71%
“…All report a high overall correlation between DNA methylation of the same samples measured using different methods. Not all of these studies commented on individual CpG site correlation, however, manual inspection of the correlation scatter plots reveal that a subset of CpGs show large differences in methylation values between the platforms being compared [1,[15][16][17][18]. Altogether, these studies demonstrate that some CpGs reproduce poorly, regardless of sample type or method used.…”
Section: Discussionmentioning
confidence: 99%